Implementasi Program Bantuan Rumah Layak Huni Untuk Masyarakat Kurang Mampu Di Kecamatan Bagan Sinembah Kabupaten Rokan Hilir Provinsi Riau - Safii Safii; Abdul Kadir; Yurial Arief Lubis (Universitas Medan Area, 2019)
The purpose of this study was, to determine the implementation of livable housing assistance in Bagan Sinembah Subdistrict along with barriers to implementation. By using a qualitative research method. The results showed that the implementation of a housing assistance program for underprivileged communities in Bagan Sinembah Subdistrict, Rokan Hilir Regency, Riau Province did not run optimally, if seen from the delivery of an incomplete socialization and not on target, and the budget in the implementation of the construction of decent housing. inadequate and lack of understanding and expertise of the implementing apparatus in development. With the Obstacles in implementing the program of housing assistance for underprivileged communities In Bagan Sinembah Subdistrict, Rokan Hilir Regency, Riau Province is related to the resources seen from human resources who do not have the expertise and ability in the construction of livable homes, not exactly the target in the implementation of development houses to the underprivileged, inadequate housing facilities are inadequate, and the lack of a budget in the construction of livable homes as well as from the bureaucratic structure dimensions related to the absence of SOPs in the construction. The conclusion obtained is that the implementation of housing assistance programs for underprivileged communities in Bagan Sinembah District, Rokan Hilir Regency, Riau Province did not run optimally.